Studi Keandalan Geolistrik Dalam Identifikasi Kebocoran Embung: Studi Kasus Embung Wolo, Sulawesi Tenggara - Mangidi, U.; Minmahddun, A.; Razak, E.N.P.; Sulha, S. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Small dams are vital for supporting water resource conservation. The reservoir stores water from several water sources, especially in the rainy season, so that it remains available in the dry season. Some reservoir infrastructures were built using earthen fill materials located around it. This condition is very vulnerable to disasters, ranging from seepage to collapse. It is important to evaluate the safety of all potential dangers to minimize the risk of disasters. One method that can be used is the geoelectric method, which allows us to analyze the resistivity properties of the soil, but the reliability of this method needs to be further evaluated. This research aims to determine the reliability of geoelectric in identifying potential leaks in reservoirs. Geoelectric measurements were carried out at Wolo Small Dam using the Wenner-Schlumberger configuration with 32 electrodes at 2.5 m. Data collection was carried out at the top of the small dam so that it could provide the condition of the soil layer of the embankment material in the longitudinal direction. Validate the measurement using the results of previous research. The results of the analysis show that there are differences in lithology in the body of the reservoir, which indicates differences in the quality of work during construction. The interface between these two surfaces can lead to leaks. Apart from that, the analysis results also show the potential for piping in the reservoir. The location of the potential piping area is not far from the results obtained in previous research at the same location. This shows that geoelectric is quite capable of being a tool that can be used to identify leaks in reservoirs or other water structures. Of course, the combination of geoelectric and other soil testing will provide better results in anticipating disasters caused by small dam leaks